Empowerment as a disabled, black woman - Oliver, Kym; Abdullahi, Jumoke (2020)
The dynamic duo of Jumoke and Kym tackle the topic of empowerment and what that means for disabled, Black women. This was filmed as part of a TEDx talk at the University of Sussex in England. _______________________________________________________________________________________________ TRIPLE CRIPPLES was created by @TheKymOliver & @JayOnLife to provide a platform for & highlight the narratives of Black & non-Black Women, Femmes & Non-Binary people of colour, living with disabilities. We are here. We exist! We know the media and mainstream disability conversations would have you believe otherwise mega eye roll*... But guess what? WE GOTS THA INTERNETS, BITCHEZZZZ!!! Eat it. *put on shades and look cool at night ———————————————————————————————- JOIN US ON OUR JOURNEY! Hit the comments box! And if you or any women/femmes/non-binary people you know, would like to be a guest... Hit the DM’s! 🖤 Website: https://thetriplecripples.uk/ Twitter/Instagram: @TripleCripples Follow Jumoke: @JayOnLife Follow Kym: @TheKymOliver ———————————————————————————————- Track: “runaway” ~ K15 feat. AMA LIVE! Big Love to K15 for kindly letting us use his amazing music as our bedding track!!! Check out @k15music, support his sound, buy some vinyls and follow him on all platforms: Twitter: @K15music Facebook: @K15music Soundcloud: @K15 Bandcamp: @K15music
Keywords: 2000 à aujourd'hui; afrique; amériques; approches et analyses; capacitisme; caraïbes; corps; cours; discours dominant; empowerment; europe; fem3300; femmes* noires; invisibilité; militance; premier cycle; périodes historiques; ressource en ligne; royaume-uni; régions géographiques; systèmes d'oppressions; thématiques

Social movements and the politics of care: Empathy, solidarity and eviction blockades - Santos, Felipe G. (Social Movement Studies, 2020)
This paper develops a perspective of mobilization based on the ethics of care to explore the complexities of political solidarity in social movements. On the one hand, it is interested in the reasons why commonly aggrieved individuals do not always collaborate to confront their oppression. On the other, it explores why sometimes people initiate mobilization for causes that do not benefit them directly. From a care perspective, aggrieved individuals may not mobilize to confront their troubles because some of their caring needs (emotional, identity, and participatory) are not covered. At the same time, empathy motivates people not affected by a grievance to initiate mobilization in support of the oppressed collective. Internal solidarity among those aggrieved may be created during the process of mobilization through care work. The analytical relevance of this model is demonstrated explaining the mobilization of the ‘Platform of Those Affected by Mortgages’, the biggest housing organization in Spain. A care-based approach to mobilization contributes to our analysis of contentious collective action by helping to better understand the complexities of political solidarity and the mechanisms through which organizations foster solidarity among their members.
Keywords: 2000 à aujourd'hui; 2010-2019; care; droit au logement; espagne; europe; militance; mouvements sociaux; périodes historiques; ressource en ligne; régions géographiques; solidarité; thématiques; étude qualitative